A Systematic Review of Drought Indices in Tropical Southeast Asia - Zaki, Muhamad Khoiru (MDPI, 2022)
This study systematically reviews the under-researched experience of performance indices to determine extreme hydroclimate in tropical Southeast Asia. The review was conducted by the Preferred Reporting Items for Systematic Review and Meta-Analysis methods with SCOPUS databases. The screening of the articles is based on the inclusion and exclusion criteria encompassing articles published between 2000 and 2021 with solely focused on three extreme hydroclimate indices (standardized precipitation index or SPI, standardized precipitation evapotranspiration index or SPEI, and palmer drought severity index or PDSI) applied in tropical Southeast Asia, and articles form in English. This study found solely 14 of the 532 articles met the criteria and those articles were analyzed thematically and synthesized narratively. The results showed the strengths of indices with the simple data input (SPI and SPEI); those indices are commonly used at the government level in Southeast Asia due to their data availability, which has Viet Nam as the highest (5 articles) number of publications, followed by Malaysia (4 articles), Thailand (3 articles), and Indonesia (2 articles). On the other hand, the sensitivity of SPI and SPEI has the limitation for specific purposes such as in the agricultural sector when applied to Southeast Asia. In the end, we highlighted the potential of future research applying quasi-biennial oscillation and South Western Indian Ocean as well as El Niño Southern Oscillation climate indices.